Detection of a Large Novel α-Thalassemia Deletion in an Autochthonous Belgian Family. (4th March 2019) - Heireman, Laura; Luyckx, Ariane; Schynkel, Katrien De; Dheedene, Annelies; Delaunoy, Mélanie; Adam, Anne-Sophie; Gulbis, Béatrice; Dierick, Johan
Abstract: α-Thalassemia (α-thal) is a common hemoglobinopathy mainly caused by deletion of one or both α-globin genes. We describe an autochthonous Belgian family diagnosed with α-thal trait. Molecular analysis revealed a novel large deletion of at least 170 kb between 226.68 kb (0.2 Mb) and 402.68 kb (0.4 Mb) from the telomere of 16p, leaving the subtelomeric region intact. The deletion includes both α-globin genes ( HBA1 and HBA2 ) but also flanking genes possibly related to non hematological effects: HBQ1, LUC7L, ITFG3, RGS11, ARHGDIG, PDIA2 and AXIN1 . These genes are not contained in the region (0.9 and 1.7 Mb from the telomere of 16p) associated with α-thal intellectual disability (ATR-16) syndrome. However, further research is necessary to exclude other potential effects than α-thal in patients with a large deletion at 0.2-0.4 Mb from the telomere of 16p. Genetic counseling is important for carriers of this deletion as homozygosity for the α-globin (– –/) haplotype may lead to Hb Bart's (γ4) hydrops fetalis syndrome.